Coiled-coil structure mediated inhibition of the cytotoxic huntingtin amyloid fibrils by an IP3 receptor fragment - Kim, Ha Neul; Park, Hye Jin; Lin, Yuxi; Cho, Taehwan; Ryu, Kyoung Seok; Won, Hyung Sik; Jin, Hyo Eon; Kim, Ji Hun; Baek, Seung Hoon; Lee, Young Ho; Seo, Min Duk (International Journal of Biological Macromolecules, 2023)
Disruption of cellular homeostasis by the aggregation of polyglutamine (polyQ) in the huntingtin protein (Htt) leads Huntington's disease (HD). Effective drugs for treating HD have not been developed, as the molecular mechanism underlying HD pathogenesis remains unclear. To develop strategies for inhibiting HD pathogenesis, the intermolecular interaction of Htt with IP3 receptor 1 (IP3R1) was investigated. Peptide (termed ICT60) corresponding to a coiled-coil motif in the C-terminus of IP3R1 was designed. Several biophysical approaches revealed the strong and specific binding of ICT60 to the N-terminal part of HttEx1. ICT60 inhibited not only amyloid formation by HttEx1, but also the cytotoxicity and cell-penetration ability of the amyloid fibrils of HttEx1. The importance of coiled–coil structure was verified by charge-manipulated variants. The coiled-coil structures of ICT60-KK and -EE were partially and largely disrupted, respectively. ICT60 wild-type and -KK inhibited amyloid formation by HttEx1-46Q, whereas ICT60-EE did not block amyloidogenesis. Similarly, the cytotoxicity and cell-penetration ability of the amyloid fibrils of HttEx1-46Q were efficiently inhibited by ICT60 wild-type and ICT60-KK, but not by ICT60-EE. We propose a mechanical model explaining how an IP3 receptor-inspired molecule can modulate cytotoxic amyloid formation by Htt, providing a molecular basis for developing therapeutics to treat HD.
Keywords: Amyloid; Exons; Huntingtin Protein; Protein Domains; Amyloid fibrillation; Coiled-coil structure; Huntington's disease; IP3 receptor fragment